Comparing Implicit and Explicit Attitudes Toward Intimate Partner Violence Against Women - Ferrer-Perez, Victoria A.; Bosch-Fiol, Esperanza; Ferreiro-Basurto, Virginia; Delgado-Alvarez, Carmen; Sánchez-Prada, Andrés (Frontiers in Psychology, 2020)
Intimate partner violence against women (IPVAW) is an epidemic social and public health problem. Research has consistently found evidence for a complex aetiology of IPVAW resulting from the interaction of many factors, among which gender-related norms and attitudes are among the main drivers of this violence. Public attitudes towards IPVAW are especially important because attitudes rejecting, condoning or fostering such behaviour are social factors that contribute to a climate of tolerance or refusal that can shape the social environment in which such violence takes place. Given the importance of these attitudes, the availability of reliable, valid and concise measures is critical for both research and intervention purposes. The evidence shows a probable bias of direct and explicit assessment measures of IPVAW attitudes, and it has been suggested that they should be complemented by indirect or implicit measures. In this context, the main aim of this paper was to examine how implicit and explicit attitudes towards IPVAW differ among a Spanish population. An opportunity sample of 693 students took part in this study. Two explicit measures (the Inventory of Distorted Thoughts about Women and Violence, IPDMV, and the Inventory of Beliefs about Intimate Partner Violence, IBIPV) and one implicit measure (the Gender Violence Implicit Association Test, a personalized form of IAT) were applied. The results obtained show that the psychometric characteristics of the implicit measure used (GV-IAT) are acceptable. Additionally, we obtained significant differences by gender, IPVAW knowledge, IPVAW involvement and political opinion when we measured IPVAW attitudes by implicit measures. However, when we measured these attitudes by explicit measures, we only obtained significant differences by gender and political opinion. Finally, the results highlight the important differences between the levels of strong IPVAW rejection measured with explicit and implicit measures, confirming the traditional discrepancy between explicit and implicit measures of attitudes. In summary, the results obtained provide additional support for the idea that GV-IT constitutes a promising assessment tool to complement explicit measures for attitudes towards IPVAW.